2022
DOI: 10.1038/s41598-021-04250-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of visual aura in migraine and probable migraine: a population study

Abstract: Visual aura (VA) presents in 98% of cases of migraine with aura. However, data on its prevalence and impact in individuals with migraine and probable migraine (PM) are limited. Data from the nation-wide, population-based Circannual Change in Headache and Sleep Study were collected. Participants with VA rating scale scores ≥ 3 were classified as having VA. Of 3,030 participants, 170 (5.6%) and 337 (11.1%) had migraine and PM, respectively; VA prevalence did not differ between these cohorts (29.4% [50/170] vs. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It is, therefore, possible that the self-reported migraine prevalence with aura does not reflect the prevalence of diagnosed migraine with aura. The prevalence of migraine with aura in the general population is 12.5% in Taiwan [ 39 ] and 29.4% in Korea [ 40 ]; however, in this study over 70% patients (Table 1 ) had reported migraine with aura at baseline. Second, the definition of a migraine day (Supplementary Table 1 ) in this study was different from the widely accepted definition that includes migraine-specific medication only.…”
Section: Discussionmentioning
confidence: 64%
“…It is, therefore, possible that the self-reported migraine prevalence with aura does not reflect the prevalence of diagnosed migraine with aura. The prevalence of migraine with aura in the general population is 12.5% in Taiwan [ 39 ] and 29.4% in Korea [ 40 ]; however, in this study over 70% patients (Table 1 ) had reported migraine with aura at baseline. Second, the definition of a migraine day (Supplementary Table 1 ) in this study was different from the widely accepted definition that includes migraine-specific medication only.…”
Section: Discussionmentioning
confidence: 64%
“…Firstly, we did not look in detail at the definition of a migraine day based on aura symptoms, but we do propose to include all days with (visual) aura symptoms lasting 5-60 minutes as migraine days (6). We solely took visual aura symptoms into account, since 98-99% of all migraine attacks with aura are accompanied by visual symptoms (20)(21)(22). Moreover, it is impossible to ask all possible aura symptomatology for each day as this is too time consuming, thus simplification of aura symptomatology for headache E-diaries is needed to lower the data entry burden for patients and thereby improve diary compliance (23).…”
Section: Effective Triptan Daysmentioning
confidence: 99%
“… 6 Visual auras are the most common type, reported to occur in 98% of cases of migraine with aura, although speech/motor and sensory symptoms can occur. 7 Auras generally occur prior to the onset of headache pain but may persist afterward. 6 One of the oldest accounts of migraine was described by Hippocrates, who wrote Most of the time he saw something shining before him like a light, usually in part of the right eye; at the end of a moment, a violent pain supervened in the right temple.…”
Section: Introductionmentioning
confidence: 99%